Revitalization of Indonesian Navy Language Education System in Promoting Human Resources Resilience - Prasetya, Heri; Khusaini, Moh; Hamamah, Hamamah; Kusumaningrum, Adi (Rekayasa, 2024)
The writer concentates on the research about Indonesian Navy language education system. The method of the research is decriptive qualitative. In resulting the outcome of education program,  there are some problem findings that are required to be solved: the education program curriculla that are still obsolete and temporary, the incompetent educators and educational staff, lack of the standardized education facilities, as well as the low intensity of education cooperation programs.The problems cause the education process of international languages not running well, so it cannot result the qualified Indonesian Navy’s graduates. To achieve the expected Indonesian Navy personnel’s graduates, the language education system in Indonesian Navy institutions can be revitalized by updating, establishing and composing the new education program curriculums, managing the human resources by adding more educators and educational staff, improving the professional development and providing more wellfare or rewards, standardizing the education facilities, such as classrooms, language laboratories, libraries, dormitories and course book references, as well as collaborating with the other foreign languange education units domestically, regionally and internationally. After that, the writer finds the strategy of revitalizing the language education system in Indonesian Navy units.  By revitalizing the system, it can result the qualified graduates of Indonesian Navy personnel that can support the Resilience of Human Resources.